The Philadelphia chromosome : a mutant gene and the quest to cure cancer at the genetic level - Wapner, Jessica (The Experiment, LLC : Distributed by Workman Pub. Co., 2013)
This work focuses on what is widely viewed as the 'poster child' of rational drug development in the cancer research world. The history of the founding of a genetic mutant chromosome in the indication of Chronic myeloid leukemia disease, and the subsequent development of "Gleevec," is the keynote of this astounding publication.